Future Meteorological Droughts in Ecuador: Decreasing Trends and Associated Spatio-Temporal Features Derived From CMIP5 Models - Campozano, Lenin; Ballari, Daniela; Montenegro, Martin; Avilés, Alex (Frontiers in Earth Science, 2020)
Droughts are one of the most spatially extensive disasters that face societies. Therefore, it’s urgent to define mitigation strategies based on objective studies. However, research of droughts features in climate change (CC) have limitations due to the phenomenon complexity and the uncertainty of future precipitation from Global Climate Models (GCMs). The study of droughts in Ecuador is limited, despite the fact that CC will have more impact on developing countries. The study aims to assess the spatio-temporal characteristics of present and future droughts in Ecuador under 4.5 and 8.5 Representative Concentrations Pathways (RCP). Due to the intricate orography of Ecuador, e.g. coast, Andes and Amazon, the 10 km dynamically downscaled results from Couple Model Intercomparaison Project 5 (CMIP5). GCMs , GISS, CSIRO, and IPSL were used to calculate the Standardized Precipitation Index (SPI) droughts (present: 1981- 2005, future: 2041- 2070). The results show that overall there is a slightly decreasing trend of future droughts occurrence in the whole country, with larger reduction, for moderate, followed by severe and extreme. The intra-annual analysis shows that in the Andes and the coast, there is a reduction of moderate and severe future droughts for 4.5 and 8.5 RCPs and all DGCMs, throughout the year; extreme drought shows small decrease to statisticaly non-significant change. In the Amazon, moderate drought for IPSL and CSIRO show some increase/decrease in the probability of occurrence from May to October/rest of the year, for severe droughts the increase/decrease is expected from May to December/from January to april, and for extreme droughts increases are expected from January to April and higher increase in October and November. Thus, in the Amazon the rainy/drier period show a decreasing/increasing trend of droughts, which may be linked wetter in wet and drier in dry paradigm, although in the Andes and the coast may be different. Knowing that CC makes more challenging decision-making and adaptation strategies, this study contributes to the spatio-temporal representation of future droughts in Ecuador, highlighting areas and months where mayor changes are expected as well as the evaluation of GCMs ability to represent droughts in tropical mountains.